Análise das relações entre os currículos pré-ativos de geografia e o Exame Nacional do Ensino Médio - ENEM: em questão a escala geográfica - Duarte, Leônidas Siqueira (2019)
The present study of the Master in Geography problematizes the relations between the official pre-active curricula for the High School and the Exame Nacional do Ensino Médio - ENEM, with respect to its geographical representations and multiscale relations in the tests, in the period 2009-2018. The objective is to argue about the possibilities and limits of the geographical scales in the ENEM and, consequently, in the school Geography, due to the influence of the exam in the teaching-learning process by its character of "curricular policy". In general, we use as a theoretical-analytical reference the triangular approach of Moreira (1997), critical theories of the curriculum and discourse analysis, based on Vilela (2013) and Foucault (2010). We rely on the reflections of scholars in the field of curriculum (MOREIRA, 1997; LOPES and MACEDO, 2011; GOODSON, 1999; APLE, 1982); of Pedagogy (SAVIANI, 2013, FRIGOTTO, 2011); Education Curriculum and Geography (ROCHA, 2013; ALBUQUERQUE, 2004; VILELA, 2013) and research in Geography (CALLAI, 2003, 2009; CASTRO, 1992, 2001; SANTOS, 2008, 2009). It was clear that the ENEM subverts the conventional logic of the classic curricular arrangements and began to play the role of curricular policy at the national level, especially after the DCNEM of 2012 (BRAZIL, 2012a). We found that the ENEM excels in the spatial-social representation of phenomena in multiple scales in 42.8% of geography items, which expresses in its curriculum policy an orientation for the exercise of transit between geographic scales in the teaching-learning process. After discussing some of the socio-spatial challenges of the exam, we propose that the ENEM Human Sciences test contemplate 75% of general items (for the whole of Brazil) and 25% of items for regional aspects, according to the region where the candidate chooses the exam. The relevance of the study is to discuss the geographic scales in the Geography curriculum and in the spatial learning, in the current context of the changes in LDBEN by means of Law nº 13.415 of February 16, 2017 (known as the law of the new High School), followed by the homologation of the Base Nacional Comum Curricular - BNCC, at the end of 2018.